2019
DOI: 10.1002/cbic.201900046
|View full text |Cite
|
Sign up to set email alerts
|

A Retro‐biosynthesis‐Based Route to Generate Pinene‐Derived Polyesters

Abstract: Significantly increased production of biobased polymers is a prerequisite to replace petroleum‐based materials towards reaching a circular bioeconomy. However, many renewable building blocks from wood and other plant material are not directly amenable for polymerization, due to their inert backbones and/or lack of functional group compatibility with the desired polymerization type. Based on a retro‐biosynthetic analysis of polyesters, a chemoenzymatic route from (−)‐α‐pinene towards a verbanone‐based lactone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 82 publications
2
39
0
Order By: Relevance
“…[13][14][15] Still, achieving controlled polymerization of pinene monomers remains a challenge, which has spurred an increased interest towards unlocking their inherent potential by activation through oxidation by chemical and biocatalytic methods. [16][17][18] Biocatalysis displays a great potential to replace harsh chemical synthesis with green options for the sustainable generation of medicines, biochemicals and materials. 19 In particular, by capitalizing on synthetic-biology approaches, mild oxidations required for monomer activation which would be challenging to access by traditional organic synthesis 20 can be achieved in water with oxygen as co-substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Still, achieving controlled polymerization of pinene monomers remains a challenge, which has spurred an increased interest towards unlocking their inherent potential by activation through oxidation by chemical and biocatalytic methods. [16][17][18] Biocatalysis displays a great potential to replace harsh chemical synthesis with green options for the sustainable generation of medicines, biochemicals and materials. 19 In particular, by capitalizing on synthetic-biology approaches, mild oxidations required for monomer activation which would be challenging to access by traditional organic synthesis 20 can be achieved in water with oxygen as co-substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The very different structural and physicochemical features (e.g., crystallinity, flexibility, and miscibility) between the original homopolymers PCL, PDL, and PNCL would yield exciting properties of their corresponding block copolymers. Others and in our recently reported work, we showed that PDL is a fully amorphous polymer with a glass‐transition temperature ( T g ) of about −57 °C . In addition, PNCL homopolymer was synthesized and characterized (Figure S5).…”
Section: Resultsmentioning
confidence: 93%
“…reported the synthesis of norcamphor lactone on 80 mmol scale, in 81% yield and 5 days reaction time which opened the door to further investigations to modulate the entire process in order to further scale it up to a better yield. We have previously reported that an engineered thermostable variant of CHMO Acineto , harboring four substitutions and referred to as CHMO Acineto _QM, was able to fully convert the nonnatural bulky substrate norcamphor (the major product is the normal lactone, 93.4%) and act on the more substituted substrate (−)‐ cis ‐verbanone . Scaling up this transformation from 2 to 33 mM of the substrate norcamphor in shake‐flask enabled the biosynthesis of norcamphor lactone in 0.5 g scale, stressing the high potential of the enzyme CHMO Acineto _QM to be used for the production of industrially relevant products (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations